Mobile health for drug dose optimisation. - Larsen, M; Farmer, A; Weaver, A; Young, A; Tarassenko, L (2011)
Mobile health monitoring in the management of long term conditions has potential benefits for patient care, especially when coupled with active adjustment of medication dosage. We report studies of patient-led self-titration of oral glucose lowering medication (OGLM) and insulin in type 2 diabetes, and dose adjustments (including dose increases) in oral chemotherapy for metastatic colorectal or breast cancer. Monitoring compliance was high in each case, and the feasibility of patients self-titrating OGLM or insulin following an agreed treatment plan was demonstrated. Chemotherapy dose increases supported by detailed toxicity profiles collected by phone have also been demonstrated.